Chitosan nanoparticles as a modified diclofenac drug release system - Duarte Junior, Anivaldo Pereira (2017)
This study evaluated a modified nanostructured release system employing diclofenac as a drug model. Biodegradable chitosan nanoparticles were prepared with chitosan concentrations between 0.5 and 0.8% (w/v) by template polymerization method using methacrylic acid in aqueous solution. Chitosan-poly(methacrylic acid) (CS-PMAA) nanoparticles showed uniform size around 50–100 nm, homogeneous morphology, and spherical shape. Raw material and chitosan nanoparticles were characterized by thermal analysis, Fourier transform infrared spectroscopy (FT-IR), and transmission electron microscopy (TEM), confirming the interaction between chitosan and methacrylic acid during nanoparticles preparation. Diclofenac sorption on the chitosan nanoparticles surface was achieved by incubation in water/ethanol (1:1) drug solution in concentrations of 0.5 and 0.8 mg/mL. The diclofenac amount sorbed per gram of CS-PMAA nanoparticles, when in a 0.5 mg/mL sodium diclofenac solution, was as follows: 12.93, 15, 20.87, and 29.63 mg/g for CS-PMAA nanoparticles 0.5, 0.6, 0.7, and 0.8% (w/v), respectively. When a 0.8 mg/mL sodium diclofenac solution was used, higher sorption efficiencies were obtained: For CS-PMAA nanoparticles with chitosan concentrations of 0.5, 0.6, 0.7, and 0.8% (w/v), the sorption efficiencies were 33.39, 49.58, 55.23, and 67.2 mg/g, respectively. Diclofenac sorption kinetics followed a second-order kinetics. Drug release from nanoparticles occurred in a period of up to 48 h and obeyed Korsmeyer-Peppas model, which was characterized mainly by Fickian diffusion transport. [Figure not available: see fulltext.].